(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
In the present paper an attempt has been made to study the distribution of dwellings and house types based on size and building materials of Chura community in village Badli. The village is located about 20 Kms southeast from Jhajjar city of Haryana state. The primary data has been collected of all the 97 households by using well prepared schedules and personal interviews have been conducted to the head of family. The village has three major scheduled castes namely Chamar, Dhanak, and Chura. Chura community is inhabited by ten clansgotras like Bagri, Lauth, Tank, Gehlot, Kudala, Chavria, Sodha, Beniwal and Bidhlan. The size of the rural dwellings denotes the economic level of the people. The two room dwellings are fairly distributed in the village with maximum number i.e. 29 (29.89 ) households while only 9 (09.28 ) dwellings occupy five more rooms.It has been observed that most of floor of the houses in the village are built of cement (55.68), followed by burnt bricks (05.16) and only 8.24 of tiles while 30.92 floor of houses are made of mud. The walls of almost all houses are (91.76 ) made of burnt bricks and only 8.24 houses are made of un-burnt bricks. It is found that most of roofs of houses (60.82 ) are built of mud and un-burnt bricks and 23 (23.71 ) roofs of the houses are made of concretes, 2.06 per cent of burnt bricks, 10.30 per cent of stones and remaining 3.10 per cent house have used tiles in the roofs. Finally, it is observed that 30 (30.92 ) houses are pacca, 59 (60.82 ) dwellings are mixed type of houses, and only eight (8.24) houses are kacha. Further, it is noted that most of pacca houses belong to Bagri and Lauth clans have good status and socially and economically better in the village. The mixed types of houses are diminishing day by day replacing into pacca houses due to the improvement in economic conditions of the inhabitants and availability and suitability of local building material in recent years.